IMPLEMENTASI VOLTAGE SENSOR DAN SENSOR INA219 SEBAGAI PENGUKUR TEGANGAN DAN ARUS PADA PEMBANGKIT LISTRIK TERMOELEKTRIK GENERATOR - Sihaloho, Arman Dwika Farlentinus Hasudungan; Rahmadewi, Reni (Peneliti.net, 2024)
Generator thermoelectric power generation system is one of the promising technologies in converting heat into electrical energy. This technology utilizes the Seebeck effect, where the temperature difference between the two ends of a thermoelectric material will generate an electric current. Even though it has great potential, the efficiency of converting heat to electricity in generator thermoelectric systems still needs to be improved. This study aims to implement voltage and current sensors, namely the voltage sensor and INA219 sensor, in a Thermoelectric Generator Power Plant (PETRIKOR) to carry out accurate measurements and monitoring of the parameters of voltage and current in the system. PETRIKOR is a thermoelectric-based power generation system that uses temperature differences to generate electrical energy. With these sensors, real-time measurements of voltage and current can be made and can help optimize PETRIKOR performance. The results of this study are expected to contribute to the development and monitoring of thermoelectric power generation systems. With accurate measurement of voltage and current.